2018
DOI: 10.3390/s18092993
|View full text |Cite
|
Sign up to set email alerts
|

A System for In-Line 3D Inspection without Hidden Surfaces

Abstract: This work presents a 3D scanner able to reconstruct a complete object without occlusions, including its surface appearance. The technique presents a number of differences in relation to current scanners: it does not require mechanical handling like robot arms or spinning plates, it is free of occlusions since the scanned part is not resting on any surface and, unlike stereo-based methods, the object does not need to have visual singularities on its surface. This system, among other applications, allows its int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Various classifications of 3D scanners have been proposed in the scientific literature [ 45 , 46 , 47 , 48 , 49 ]. Figure 3 shows a classification of 3D scanners, which is adopted in the context of this article.…”
Section: Scanner-based 3d Modelingmentioning
confidence: 99%
“…Various classifications of 3D scanners have been proposed in the scientific literature [ 45 , 46 , 47 , 48 , 49 ]. Figure 3 shows a classification of 3D scanners, which is adopted in the context of this article.…”
Section: Scanner-based 3d Modelingmentioning
confidence: 99%
“…However, the 3D evaluation is not reliable as it does not have a ground truth to verify. Perez-Cortes et al [ 10 ] also follows a similar strategy, but instead of using a pointer, a sphere is used in 16 positions, and it is solved through a set of camera projections of the epipolar lines. Robson et al [ 11 , 12 ] carried out a photogrammetric calibration procedure (bundle adjustment) through the Manhattan Vision Metrology System (VMS) pattern to solve intrinsic parameters, extrinsic parameters, and 3D coordinates in one go.…”
Section: Introductionmentioning
confidence: 99%
“…Perez et al [ 15 ] calibrate it using two spheres and Zhang et al [ 16 ] follow planar pattern methodologies to calibrate both intrinsic and extrinsic parameters. Planar pattern calibration techniques where chess boards [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ] or other types of 3D patterns [ 10 ] are used have limitations in terms of high-range scenarios as very large patterns would be requested and all cameras can see the same work areas. In this sense, contributions such as Xing et al’s.…”
Section: Introductionmentioning
confidence: 99%
“…Other systems make use of robotic arms to move the object in front of a sensor such as Fei et al [ 4 ] or Brosed et al [ 5 ]. It is also possible to obtain the 3D reconstruction from multiple views as Perez-Cortes et al [ 6 ] show. In Bi et al [ 7 ] a survey of non-contact 3D scanners with a classification of their technologies from a manufacturing perspective is presented.…”
Section: Introductionmentioning
confidence: 99%
“…Although the results of this work are generalizable, the experiments presented use a 3D reconstruction technique from multiple silhouettes as explained in Perez-Cortes et al [ 6 ] and 3D models acquired with a ZG3D patented device [ 11 ] as the one shown in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%